Relationships between disordered eating, body dissatisfaction, and low energy availability in women collegiate athletes - Fields, J. B.; Jones, M. T.; Kitts, S. E.; King, E. L.; Jagim, A. R. (The Journal of Strength and Conditioning Research, 2026)
Women collegiate student-athletes face unique challenges regarding nutrition, body image, and athletic performance, increasing their risk for low energy availability (LEA), disordered eating (DE), and body dissatisfaction (BID). However, limited data exist exploring LEA, DE, and BID across a variety of women's sports. Therefore, the purpose of this study was to evaluate the prevalence of and relationships among LEA risk, DE behaviors, and BID in women collegiate athletes from multiple sports. Division I, II, and III women student-athletes (n = 115) participated in this cross-sectional, descriptive study. Athletes completed the low energy availability for females questionnaire (LEAF-Q), eating attitudes test (EAT-26), muscularity-oriented eating test (MOET), and body dissatisfaction items from the eating disorder examination questionnaire (EDE-Q) to assess LEA risk, DE behaviors, and BID, respectively. Sixty-four percentages of athletes were at risk for LEA, with the highest prevalence in volleyball (100%), wrestling (68%), lacrosse (67%), and cross country (57%). However, only 8% of athletes were classified at risk for eating disorders. Notably, 81 and 84% of athletes reported body weight and shape dissatisfaction, respectively, which was strongly associated with disordered eating behaviors (EAT-26: r = 0.707; MOET: r = 0.723, p < 0.001). These results show a high prevalence of LEA risk and BID across athletes, with DE behaviors strongly linked to body image concerns. Despite a high LEA risk among athletes, clinical eating disorder risk remained low, suggesting that undereating may often be unintentional. Targeted interventions focused on nutritional education, body image, and psychological support are critical for improving health and performance outcomes among collegiate women student-athletes.